Funding in the budgetary institution as a factor of staff satisfaction - V. E. Gladkova; E. I. Gubaydullina; I. O. Mikhailov (Путеводитель предпринимателя)
The article considers the peculiarities of labor financing in a budgetary institution through the lens of staff satisfaction with working conditions, which is one of the priority goals of the organization’s personnel policy. The article presents a methodology for assessing staff satisfaction with work in a budget institution, which allows you to identify «problem zones» and improve working conditions. The authors tested the proposed technique. The proposed methodology is based on a comprehensive approach, which takes into account working conditions, financing, labor content and interaction of employees within the structural unit. As a result of the development of the methodology, a model of interaction of the department with other structural divisions of the educational organization was proposed.The purpose of the model is to identify relationships between business units to optimize and balance the interests of all participants. The interaction of structural divisions is carried out with the aim of organizing the educational process and research activities, exchanging experience, building interdisciplinary ties, and implementing comprehensive scientific research. The organization of interaction between faculties allows you to integrate the research base an